RECYCLING OF MIXED POLYOLEFIN WASTES - Toldy, Andrea; Bodzay, Brigitta; Tierean, Mircea (OAIMDD - EcoZone Publishing House, 2009)
The mass of usage of secondary plastics are mostly determined by their quality and price. Therefore it was essentially to collect and evaluate the related aspects and expectations from the potential secondary-plastics users. To enable this in the frame of the W2Plastics EU7 project (Magnetic Sorting and Ultrasound Sensor Technologies for Production of High Purity Secondary Polyolefins from Waste) an adequate questionnaire was worked and sent out to automotive plastics end-product manufacturers. With the evaluation of these questionnaires basic parameters for the technology development in the frame of W2Plastics project were determined.
Keywords: market analysis; mixed polyolefin waste; recycling of plastics